MAHASISWA DAN PELESTARIAN LINGKUNGAN - Ibnu Luthfi, Christo David Mangasi Siregara, Perina Imatur Rahma, Elli Cahaya Nurani S, Mhd. Hafiz F (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2025)
Environmental preservation is a global issue that is still relevant to study, especially in relation to the responsibilities of the younger generation, especially students. This article examines the role of student social networks in preserving the environment and the obstacles they face. The data in this article was obtained through a study of several literature such as articles, books and cases published on social media and mass media; field surveys of the environment experiencing pollution and destruction; interviews with students who were informants; observations of student activity programs in environmental conservation. The location of this research is at Medan State University and involves several internal campus student organizations. These include the Student Association for Anthropology Education, Geography Education, Biology Education, Chemistry Education, as well as the Nature Lover Student Activity Unit.